Potsdamer Platz Reconstruction - Renzo Piano (Oz, 2001)
Shortly after the reunification of Germany numerous architectural competitions were held in connection with plans to renovate Berlin. One such project sponsored by Daimler-Chrysler involved the rehabilitation of the square, Potsdamer Platz.